Next generation antithrombotic therapy: focus on antisense therapy against coagulation factor XI - Lippi, Giuseppe; Harenberg, Job (Seminars in thrombosis and hemostasis, 2015)
Although the current therapeutic armamentarium of venous thrombosis encompasses the use of vitamin K antagonists, heparins, and direct oral anticoagulants, these drugs have several important drawbacks. Antisense oligonucleotides are relatively short single-stranded nucleic acid sequences, which hybridize with a target messenger RNA (mRNA) and suppress protein synthesis. Coagulation factor XI is a key player in blood coagulation, and thus represents a potential target for antisense therapy. The available evidence reviewed in this article suggests that factor XI antisense oligonucleotides may be more effective than conventional anticoagulants in preventing the onset and propagation of thrombosis, do not require factor measurement since the reduction of mRNA synthesis appears dose-dependently, robustly, and stably decreased for 3 to 5 weeks after the end of administration, with an incidence of major bleeding that is at least not greater than that associated with warfarin or low-molecular-weight heparin therapy. Despite conceptual simplicity, rational design, and relatively inexpensive cost, the preliminary findings in animal models and in patients undergoing knee surgery need to be validated in other prospective trials and cost-effective analyses before this attractive treatment option can be advocated as a new paradigm in prevention and treatment of venous thrombosis.
Gesehen am 25.10.2017